Language, Power, and Misinformation: A Mixed-Method Analysis of COVID-19 Discourses on Norwegian Twitter - Siri Frisli (Social Media + Society, 2025)
This study investigates COVID-19-related misinformation on Norwegian Twitter (X), using a mixed-method approach to analyze a large corpus of 426,000 Norwegian-language tweets posted over the course of 3 years, focusing on the interplay between discursive strategies, ideological dynamics, and power relations. The quantitative analysis uses Structural Topic Modeling (STM) to identify and map the prevalence of key discourses. The STM revealed how the COVID-19 misinformation on the platforms was mainly concentrated around two discourses: politics and health. A qualitative critical discourse analysis was used to explore how vaccine-related misinformation reinforced or challenged broader power dynamics and hegemonic ideologies around health, science, and freedom. Informed by the quantitative analysis, the discourse analysis focused on two prevalent misinformation topics, revealing how vaccine-critical discourses contest the authority of health institutions and the government by framing vaccines as dangerous, experimental, and illegal. These findings contribute to the broader understanding of how misinformation circulates and evolves in specific sociopolitical contexts. By analyzing the intersections of ideology, power, and discourse, the study highlights social media’s role in mediating public debates during health crises. The results emphasize that misinformation is not merely false or misleading information but a strategic challenge to hegemony, ideology, and power. Implications include the need for more nuanced approaches to combating misinformation, addressing its ideological and discursive appeal.